Between observer repeatability of sputum differential cell counts. Influence of cell viability and squamous cell contamination - Ward, R; Woltmann, G; Wardlaw, A; Pavord, I (1997)
Induced sputum differential cell counts have been advocated as a method of non-invasively assessing airway inflammation in asthma and other airway diseases. Relatively little is known about the between observer repeatability of sputum differential cell counts and the factors that influence it. We have assessed the between observer variability of induced sputum inflammatory cell counts in 42 slides from 38 patients (31 with asthma, 7 normal subjects). Sputum was induced and processed as suggested by Pizzichini et al (Am J Respir Crit Care Med 1996;154:308-17). Slides were classified as good (<20% squamous cells and >60% viability; n=20); low viability (<60% viability; n=14) and high squamous cell contamination (>20% squamous cells; n=8). Two blinded observers counted betwen 200 and 400 non-squamous cells in each slide and agreement was assessed by the intraclass correlation coefficient (ICC) and the standard deviation of between observer differences (SD). Between observer repeatability was as follows: Category Eosinophil* Macrophage Neutrophil Overall ICC 0.90 0.89 0.90 SD 0.27 11.2 11.0 Good ICC 0.96 0.94 0.93 SD 0.17 9.3 10.5 Viability <60% ICC 0.85 0.94 0.91 SD 0.35 8.8 7.6 Squamous >20% ICC 0.85 0.25 0.55 SD 0.29 15.7 16.1 * Log SD We have shown that the overall between observer repeatability of differential cell counts is good. Low cell viability and particularly excess squamous cell contamination reduce between observer repeatability suggesting that techniques that ensure high cell viability and reduce squamous contamination would be an advantage.